Acts of distinction at times of crisis: an epistemological challenge to intercultural communication research. (4th May 2022) - Hua, Zhu; Jones, Rodney H.; Jaworska, Sylvia
ABSTRACT: In this article, we reflect on the epistemological frameworks and priorities of intercultural communication research regarding 'cultural differences'. With the current challenge posed by the COVID-19 pandemic, along with the growing political and social polarisation in recent years, we argue for a need to (re)focus attention to the ways acts of distinction (i. e., the explicit marking and accentuating of cultural differences) function in everyday encounters. The notion of acts of distinction, supported with principles from interactional sociolinguistics and moment analysis, can further our understanding of the dynamics of domination and the symbolic dimensions of group formation.